Analisis Yuridis Tentang Fenomena Tirhadap Tindak Pidana Penganiayaan Mengakibatkan Luka Berat Yang Dilkukan Penagih Hutang - M.Gholam Ghazali; M.Teguh Febriana K.J (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Offense description is one of the areas of criminal law. Torture under the Criminal Code is generally defined as a criminal act against the body. All criminal acts regulated in the Criminal Code also have criminal threats specified. Likewise with interpretation offenses and murder offenses. The criminal penalties for these two offenses refer to the Criminal Code book I chapter II concerning crimes, especially in article 10. As for the means, in examining and proving the Public Prosecutor's accusations, the Panel of Judges must be more careful in giving considerations and concluding a criminal act. So that acts of fraud can truly provide fair decisions and not harm or benefit anyone so that acts of forgiveness receive sanctions in accordance with the applicable laws and regulations.